JENIS-JENIS PAKU TERESTERIAL DI KAWASAN CAGAR ALAM LEMBAH ANAI KABUPATEN TANAH DATAR SUMATERA BARAT - Andrian, Noki; Abizar, Abizar; Hernawati, Hernawati (STKIP PGRI Sumbar, 2014)
AbstractÂ Ferns specially have distinctive physique , make likely to be mistake with other plant species . Part of the uniqueness of it is that there are young leaves are curled which will open if an adult , this characteristic also called vernasi curled , nails reproduce by spores , spores are formed within the sporangium is generally found in large numbers on the underside of leaves .Anai Valley Nature Reserve is a conservation area located in West Sumatra . This research was carried out by using descriptive method by means of direct field observation and collection . Identification is done in Sumatra Biota Laboratory , University of Andalas (ANDA) , Biological Resources Unit of Sumatra , Campus Unand Limau Manis , Padang .From the research that has been conducted in the area Anai Valley Nature Reserve , Tanah Datar regency of West Sumatra , which is classified into sixteen kinds of nails , grouped into thirteen families , eight orders , and three classes of terrestrial nails .